The dose-dependent impact of γ-radiation reinforced with backscatter from titanium on primary human osteoblasts - Lisa Printzell; Janne Elin Reseland; Nina Frederike Jeppesen Edin; Hanna Tiainen; Jan Eirik Ellingsen (Biomaterial Investigations in Dentistry, 2023)
AbstractIn head and neck cancer patients receiving dental implants prior to radiotherapy, backscatter from titanium increases the radiation dose close to the surface, and may affect the osseointegration. The dose-dependent effects of ionizing radiation on human osteoblasts (hOBs) were investigated. The hOBs were seeded on machined titanium, moderately rough fluoride-modified titanium, and tissue culture polystyrene, and cultured in growth- or osteoblastic differentiation medium (DM). The hOBs were exposed to ionizing γ-irradiation in single doses of 2, 6 or 10 Gy. Twenty-one days post-irradiation, cell nuclei and collagen production were quantified. Cytotoxicity and indicators of differentiation were measured and compared to unirradiated controls. Radiation with backscatter from titanium significantly reduced the number of hOBs but increased the alkaline phosphatase activity in both types of medium when adjusted to the relative cell number on day 21. Irradiated hOBs on the TiF-surface produced similar amounts of collagen as unirradiated controls when cultured in DM. The majority of osteogenic biomarkers significantly increased on day 21 when the hOBs had been exposed to 10 Gy, while the opposite or no effect was observed after lower doses. High doses reinforced with backscatter from titanium resulted in smaller but seemingly more differentiated subpopulations of osteoblasts.